KAJIAN KEBERLANJUTAN PENGELOLAAN LINGKUNGAN PELABUHAN KOTA MEULABOH (STUDI KASUS : PELABUHAN UMUM DIUSAHAKAN) - Anhar Rozi (JURNAL PERIKANAN TROPIS, 2018)
The port was facility at the end of ocean, river, or lake for ship received and cargo moving as well as passanger to into it. The aimed of this study was knowing the extent to which the enviroment management Meulaboh city port assessed from ecological, economic, socio-cultural and institutional dimensions. The method in this study was conducted with descriptive. Value of IkB-LOLINGPEL was 20.5, while the value of the index dimensions ecological, economic, socio-cultural and institutional environment in the Meulaboh city port were 20.00, 76.00, 60.30 and 53.14 respectively. The results of statistical tests Rap-LOLINGPEL method was good enough to be used as a tool to evaluate the environmental management port in an area or region quickly (rapid apprissial).Keywords: IkB-LOLINGPEL, port, Rap-LOLINGPEL